Preliminary study of the role of social support in cycles of intimate partner violence - Dany Laure Wadji; Rachel Langevin (European Journal of Psychotraumatology)
Background: Parents’ experiences of IPV are associated with an increased risk for their children to experience IPV. However, the factors that may contribute to intergenerational IPV, particularly between adult mothers and daughters, are still poorly understood. To fill this gap in the literature, this preliminary study examines the moderating role of social support in IPV cycles among Cameroonian mother-daughter dyads.Method: Sixty-one mother-daughter dyads completed questionnaires individually. We performed moderation analysis to examine if the association between mothers’ experiences of IPV and daughters’ experiences of IPV was moderated by daughters’ social support.Results: Results showed that social support influences the strength of the association between mothers’ and daughters’ IPV victimization. As levels of social support reported by daughters increased, the strength of the association between their and their mothers’ experiences of IPV victimization decreased. At high levels of social support, this association was no longer significant (b = 0.09, SE = 0.27, t = 0.34, p > .05).Conclusion: Support from family and friends is important in contexts of intergenerational IPV; thus, interventions aimed at preventing and reducing IPV may aim to strengthen these informal support systems to mitigate the effect of IPV.